(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article provides a comprehensive analysis of the significance of latin terminology in clinical diagnosis. it explores the historical development of latin-based medical nomenclature, its function in ensuring anatomical precision, and its role in standardizing disease names. the study highlights the importance of latin terms in clinical documentation, laboratory and instrumental reports, and pharmaceutical prescriptions. furthermore, it emphasizes how the consistent use of latin contributes to greater diagnostic accuracy, reduction of medical errors, and enhancement of international communication among healthcare professionals.